Effect of adjuvant radiotherapy after breast-conserving surgery in elder women with early-stage breast cancer: a propensity-score matching analysis - Han, Tingting; Shi, Mingwei; Chen, Qiwei; Chen, Dongbo; Hao, Jiqing (Frontiers in Oncology, 2023)
Purpose The study aimed to explore the role of adjuvant radiotherapy (RT) after breast-conserving surgery (BCS) in elder women with early-stage breast cancer (BC). Methods BC patients with 70-79 years of age, stage T1‐2N0‐1M0, undergoing BCS were screened in the Surveillance, Epidemiology and End Results (SEER) database between 2010 and 2015. The clinicopathological characteristics were balanced with propensity-score matching (PSM) method. Kaplan–Meier curves and Cox regression analyses were performed to determine the impact of adjuvant RT on BC patients. Results Ultimately, 12,310 patients treated with adjuvant RT and 4837 patients treated with no RT, were involved in the analysis. Overall, patients treated with adjuvant RT was associated with a better breast cancer-specific survival (BCSS) (HR: 1.980 [1.596- 2.456], P < 0.001) and overall survival (OS) (HR: 2.214 [1.966- 2.494], P < 0.001) than those who did not undergo RT. After 1:1 PSM, adjuvant RT still performed advantage in both BCSS (HR: 1.918 [1.439- 2.557], P < 0.001) and OS (HR: 2.235 [1.904- 2.624], P < 0.001). In the multivariate COX analysis of BCSS, widowed, divorced and separated patients, tumor grade III, T2 stage, N1 stage, no RT, molecular subtypes with luminal B and triple negative were associated with a shorter BCSS (P < 0.05). In the multivariate COX analysis of OS, age ≥74 years, widowed, divorced and separated patients, tumor grade II/III, T2 stage, no RT, no chemotherapy, molecular subtypes with triple negative were associated with a shorter OS (P < 0.05). Furthermore, the advantages of adjuvant RT were observed in all subgroup analysis. Conclusion Adjuvant RT after BCS can improve both BCSS and OS in elderly patients with early-stage BC. Additionally, all subgroups analysis-derived BCSS and OS were in support of RT.